A Retrospective Analysis of Tuberculosis Patients Treated in Diyarbakır Tuberculosis Control Dispansary No 1 in 2004 - Ateş, Güngör; Ataman, Arzu; Ekinci, Şenay (Fırat University, 2007)
Objective: We aimed to evaluate the demographic data, diagnostic methods, results of treatment, history of contact and bacteriological situation of the patients whom was treated with the diagnosis of tuberculosis in Diyarbakir Control Dispensary No 1 in 2004 (year). Materials and Methods: In this study, 306 patients with tuberculosis who were treated in Diyarbakir Control dispensary No 1 from January 2004 to December 2004 were assessed retrospectively. Results: One hundered sixty five (53.9%) of our cases were males, 141 (46.1%) were females, and the mean age was 28,92±16,73. Most of our patients (87.6%) were composed of people who admitted to our dispansary with some complaints and others were diagnosed by some screening tests applied among people (11.8%) who had close contact with tuberculous patients. One hundered sixty nine (55.2%) patients had pulmonary tuberculosis and 137 (44.8%) cases had extrapulmonary tuberculosis. Acid fast bacilli (ARB) at sputum was positive in 72.8% of the pulmonary TB cases before the treatment. Seventy eigth percent of patients (with TB) had completed their treatments regularly. Fourteen (8.3%) patients were cured. Conclusion: Although the proportion of patients completing the treatment was not low, the proportion of cure was very low. According to our results bacteriological methods should be used not only during the diagnosis but also during the follow up of treatment. ©2007, Firat University, Medical Faculty

Amaç: Diyarbakır 1 No'lu Verem Savaşı Dispanseri'nde 2004 yılında tüberküloz tanısı ile tedaviye alınan hastaların demografik bilgilerini, tanı konma yöntemleri, temas durumları, tedavi sonuçlarını ve bakteriyolojik durumlarını değerlendirmek. Gereç ve Yöntem: Ocak- Aralık 2004 tarihleri arasında Diyarbakır 1 No'lu Verem Savaş Dispanseri'nde kayıtlı 306 tüberküloz hastasının dosyaları retrospektif olarak incelendi. Bulgular: Hastaların 165'i (%53.9) erkek, 141'i (%46.1) kadın ve yaş ortalaması 28,92±16,73 idi. Olguların 268'i (%87.6) ferdi başvuru ile, 36'sı (%11.8) temaslı taraması ile tespit edilmişti. Tüberküloz hastası ile temas öyküsü 74 (%24.2) hastada mevcuttu. Olguların 169'u (%55.2) akciğer tüberkülozu, 137'si (%44.8) akciğer dışı tüberküloz olgularından oluşuyordu. Tanı aşamasında akciğer tüberkülozlu olguların 148'ine (148/169) yayma bakılmış olup, bunlardan 123'ü (%72.8) pozitif bulunmuştu. İdame döneminde en az iki kez aside dirençli bakteri (ARB) bakılarak tedavinin sonlandırıldığı (kür) olgu sayısı 14 (%8.3) idi. Tedaviyi tamamlama %78.7 (133 hasta) olarak bulundu. Sonuç: Tedaviyi tamamlama oranları görece yüksek olmasına rağmen, kür oranları çok düşüktür. Mevcut bulgular bakteriyolojik yöntemlerin tanı aşamasında olduğu kadar tedavi süresince de kullanılması gerektiğini düşündürmektedir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Diyarbakır 1 No'lu Verem Savaşı Dispanseri'nde 2004 Yılında Tedaviye Alınan Tüberküloz Olgularının Retrospektif Olarak Değerlendirilmesi